Perbedaan Jumlah Koloni Bakteri Subgingiva Setelah Menyikat Gigi dengan Berbagai Pasta Gigi yang Mengandung Bahan Herbal Sirih (Peper betle Linn.), Siwak (Salvadaro persica) dan Cengkeh (Eugenia caryophyllus) pada Anak dengan Disabilitas Intelektual - Fitria, Karin Tika; Gumilar, Mira Sri (Universitas Batanghari Jambi, 2024)
Children with Intellectual Disabilities have a higher risk of oral diseases such as dental caries and periodontal diseases compared to other children. Therefore, efforts are needed to help maximize the prevention of these diseases. The abundance of herbal materials in the community, which have been proven to have antibacterial effects, has been increasingly formulated into toothpaste. This is expected not only to provide a mechanical cleaning effect on plaque but also to have antibacterial effects and inhibit plaque growth for a longer period in the oral cavity.This research aims to determine the difference in subgingival bacterial colonies after brushing teeth with various herbal-containing toothpaste in children with intellectual disabilities. The study was conducted using a quasi-experimental pre-post control group design. Subgingival fluid samples were taken from respondents aged 6-12 years before and after brushing their teeth with four groups: (K) without toothpaste, (A) toothpaste containing betel leaves (Piper betle Linn.), (B) toothpaste containing Miswak (Salvadora persica), and (C) toothpaste containing Clove (Eugenia caryophyllus). The samples were then cultured in Plate Count Agar media for 48 hours. Colony counting was performed using the Total Plate Count (TPC) method with a Colony Counter. Statistical analysis was conducted using Wilcoxon and Kruskal-Wallis tests.The results of the study showed a decrease in the number of CFUs (colony-forming units) after brushing teeth. Significant reductions were obtained in toothpaste B (p-value = 0.046) and toothpaste C (p-value = 0.028). In conclusion, toothpaste containing Miswak and Clove effectively reduces the number of bacterial colonies formed in subgingival fluid samples..